RAPAPPORT’S BROTH , A BETTER ENRICHMENT MEDIUM IN THE IDENTIFICATION OF SALMONELLA FROM PROCESSED FROG LEGS - RAJAGOPALAN, D; DESPANDE, C K; JOSHI, LEELA (Fishery Technology, 2017)
Salmonella serotypes recovered from processed frog legs were compared on three enrichment media,Selenite cystine broth (SC),Tetrachionate broth (TT) and Rapapports broth (RB) 25/37Â°C after pre-enrichment in lactose broth. The studies indicate that enrichment media RB 25/37Â°C is superior to SC broth as well as TT broth. TT broth facilitated more of Salmonella serotypes to grow, where as SC broth enabled different groups of salmonella serotypes to grow.